2013
DOI: 10.1002/anie.201210020
|View full text |Cite
|
Sign up to set email alerts
|

Photoassisted Generation of a Dinuclear Iron(III) Peroxo Species and Oxygen‐Atom Transfer

Abstract: Nature has developed a large variety of metalloenzymes capable of catalyzing selective oxidation reactions through the reductive activation of dioxygen at mono-or dinuclear iron active sites. [1][2][3][4] Among these metalloenzymes, cytochromes P 450 (cytP 450 ), with a mononuclear iron active site, are the most widely known and studied, whereas soluble methane monooxygenase (MMO), which contains a dinuclear iron center, is under intensive investigation.[5] Both systems oxidize a variety of organic substrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…UV/Vis spectroscopy showed the reaction to be complete within several minutes, and analysis of a reaction carried out at –78 °C showed that a sulfinato‐iron(III) compound is formed as the first intermediate. Unfortunately, a potential µ‐peroxido‐diiron(III) intermediate such as reported in another study was not observed in our reactions …”
Section: Discussionmentioning
confidence: 99%
“…UV/Vis spectroscopy showed the reaction to be complete within several minutes, and analysis of a reaction carried out at –78 °C showed that a sulfinato‐iron(III) compound is formed as the first intermediate. Unfortunately, a potential µ‐peroxido‐diiron(III) intermediate such as reported in another study was not observed in our reactions …”
Section: Discussionmentioning
confidence: 99%
“…Reductive activation of O 2 in a nonenzymatic system was reported for a diiron(III) complex and a ruthenium(II)-polypyridine-type complex, which acts as a photosensitizer, and triethylamine (TEA), which functions as a sacrificial electron donor [26]. Exposure of the photogenerated diiron(II) complex to O 2 leads to the formation of the diiron(III)-peroxo intermediate responsible for oxygen-atom transfer to triphenylphosphine to produce triphenylphosphine oxide.…”
Section: Photoinduced Electron-transfer Catalysis Of P450 Via Reductimentioning
confidence: 99%
“…Given the importance of this issue, many methods have been extended in these topics. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Despite their signicant results, phosphine oxidation reactions have some problems. A catalytic or stoichiometric amount of additives must be added to initiate or catalyze this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more efficient reactions that can be performed under ambient conditions are in urgent need considering the increasing environmental concerns. Photooxidation [23][24][25][26][27][28][29] provides an efficient way to realize this reaction, which normally uses oxygen as the oxidant. [25][26][27] Gold catalysis has quickly become a hot topic in Chemistry in the past decade.…”
Section: Introductionmentioning
confidence: 99%